IDENTIFICATION OF PSYCHOLOGICAL STATUS AS AN EFFORT TO DEVELOP COMMUNITY-BASED HIV/AIDS CLIENT REHABILITATION MODEL - Nur Widayati; Murtaqib (Program Studi Ilmu Keperawatan Universitas Jember, 2016)
Stigma and discrimination can hinder the prevention and treatment of HIV/AIDS and give psychological impact that can lower quality of life of people living with HIV/AIDS. Community-based HIV/AIDS client rehabilitation model can be used as an approach or strategy to address the stigma and discrimination towards HIV/AIDS. Development of the model requires identification of psychological status of the patients such as family support, the level of depression, and quality of life. Eleven HIV/AIDS patients diagnosed in VCT Clinic of Public Health Center of Tanggul were enrolled in this study by applying purposive sampling technique. Data were collected between August and September 2015 by using WHO QOL-BREF questionnaire to measure quality of life, Beck depression